Feminist Collections, v.18, no.4 (summer 1997) - (:unkn) unknown (My University, 1997)
Subtitle: A Quarterly of Women's Studies resources. 51p.
Special Issue: Women in the U.S. West and Midwest. FROM THE EDITORS. BOOK REVIEWS: The Hearts and Voices of Midwestern Prairie Women by Barbara Handy-Marchello. Not Just White and Protestant: Midwestern Jewish Women by Susan Sessions Rugh. Beyond Bars and Beds: Thriving Midwestern Queer Culture by Meg Kavanaugh. Multiple Voices: Rewriting the West by Mary Neth. The Many Meanings of Difference by Mary Murphy. Riding Roughshod or Forging New Trails? Two Recent Works in Western U.S. Women's History by Katherine Benton. FEMINIST VISIONS: Flipping the Coin of Conquest: Ecofeminism and Paradigm Shifts by Deb Hoskins. FEMINIST PUBLISHING. WORLD WIDE WEB REVIEW: EATING DISORDERS ON THE WEB: by Lucy Serpell. COMPUTER TALK: Compiled by Linda Shult. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Reviewed by Phyllis Holman Weisbard and others. PERIODICAL NOTES: Compiled by Linda Shult. ITEMS OF NOTE: Compiled by Amy Naughton. BOOKS RECENTLY RECEIVED. SUPPLEMENT: INDEX TO VOLUME 18.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews; Women in the U.S.; Women in the Midwest; Ecofeminism; Eating Disorders